The Affordable Care Act Contraception Mandate & Unintended Pregnancy in Women of Reproductive Age: An Analysis of the National Survey of Family Growth, 2008-2010 v. 2013-2015 - MacCallum-Bridges, Colleen L. (Contraception, 2019)
OBJECTIVE(S): The contraception mandate of the Affordable Care Act (ACA) could reduce unintended pregnancies by increasing access and affordability of contraceptive resources, such as long-acting reversible contraceptives (LARCs). The objective of this study was to assess: (1) whether unintended pregnancies decreased following the contraception mandate, and (2) whether this decrease differed by demographic characteristics (race/ethnicity, insurance, or relationship status). STUDY DESIGN: We used data on sexually active, fecund women of reproductive age from the National Survey of Family Growth (NSFG) (unweighted n=7,409). We used logistic regression to compare odds of unintended pregnancy between pre-mandate (2008–2010) and post-mandate (2013–2015) periods, both overall and stratified by demographic characteristics. RESULTS: Paralleling an increase in LARC use (p<0.01), the percentage of women experiencing unintended pregnancy in the prior year decreased from 5.5% to 4.9% (p=0.45), and the percentage of pregnancies that were unintended in the prior year decreased from 44.7% to 37.9% (p=0.21) following the mandate. Overall, the odds of experiencing unintended pregnancy decreased 15% from the pre-mandate to post-mandate period (OR: 0.85, 95% CI: 0.62, 1.17; p=0.32), with the greatest reduction in odds observed in women with government-sponsored insurance (OR: 0.63, 95% CI: 0.41, 0.97; p=0.04). CONCLUSIONS: Unintended pregnancy decreased in NSFG respondents in the two years following the contraception mandate, but this observation may have been due to chance. The current study, however, is limited by its early study period which could under-estimate the mandate’s full effect. More effort is required to identify and address additional barriers to contraception and reproductive autonomy.